Clinical Pharmacology, Toxicity, and Abuse Potential of Opioids. (15th August 2021) - Vearrier, David; Grundmann, Oliver
Abstract: Opioids were the most common drug class resulting in overdose deaths in the United States in 2019. Widespread clinical use of prescription opioids for moderate to severe pain contributed to the ongoing opioid epidemic with the subsequent emergence of fentanyl‐laced heroin. More potent analogues of fentanyl and structurally diverse opioid receptor agonists such as AH‐7921 and MT‐45 are fueling an increasingly diverse illicit opioid supply. Overdose from synthetic opioids with high binding affinities may not respond to a typical naloxone dose, thereby rendering autoinjectors less effective, requiring higher antagonist doses or resulting in a confusing clinical picture for health care providers. Nonscheduled opioid drugs such as loperamide and dextromethorphan are associated with dependence and risk of overdose as easier access makes them attractive to opioid users. Despite a common opioid‐mediated pathway, several opioids present with unique pharmacodynamic properties leading to acute toxicity and dependence development. Pharmacokinetic considerations involve half‐life of the parent opioid and its metabolites as well as resulting toxicity, as is established for tramadol, codeine, and oxycodone. Pharmacokinetic considerations, toxicities, and treatment approaches for notable opioids are reviewed.